Pregnancy outcome in women with polycystic ovarian syndrome. - Dr. SAKEENA, Mumtaz, Nousheen khaleeq, AMBREEN NAZ, Hafiza Khatoon, RAISHEM ALI, Naseem mallah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
PCOS, or polycystic ovary syndrome, is a common hormonal disorder among women of reproductive age. PCOS can have a significant impact on fertility, leading to difficulties in conceiving and carrying a pregnancy to term. Pre-pregnancy, antenatal, and intrapartum care should focus on reducing these risks